A comparison of the surgical mortality due to colorectal perforation at different hospitals with data from 10, 090 cases in the Japanese National Clinical Database. Issue 2 (January 2017) - Ohki, Takeshi; Yamamoto, Masakazu; Miyata, Hiroaki; Sato, Yasuto; Saida, Yoshihisa; Morimoto, Tsuyoshi; Konno, Hiroyuki; Seto, Yasuyuki; Hirata, Koichi
Abstract : Abstract: Colorectal perforation has a high rate of mortality. We compared the incidence and fatality rates of colorectal perforation among different hospitals in Japan using data from the nationwide surgical database. Patients were registered in the National Clinical Database (NCD) between January 1st, 2011 and December 31st, 2013. Patients with colorectal perforation were identified from surgery records by examining if acute diffuse peritonitis (ADP) and diseases associated with a high probability of colorectal perforation were noted. The primary outcome measures included the 30-day postsurgery mortality and surgical mortality of colorectal perforation. We analyzed differences in the observed-to-expected mortality (O/E) ratio between the two groups of hospitals, that is, specialized and non-specialized, using the logistic regression analysis forward selection method. There were 10, 090 cases of disease-induced colorectal perforation during the study period. The annual average postoperative fatality rate was 11.36%. There were 3884 patients in the specialized hospital group and 6206 in the non-specialized hospital group. The O/E ratio (0.9106) was significantly lower in the specialized hospital group than in the non-specialized hospital group (1.0704). The experience level of hospitals in treating cases of colorectal perforation negatively correlated with the O/E ratio. We conducted the first study investigating differences among hospitals with respect to their fatality rate of colorectal perforation on the basis of data from a nationwide database. Our data suggest that patients with colorectal perforation should choose to be treated at a specialized hospital or a hospital that treats five or more cases of colorectal perforation per year. The results of this study indicate that specialized hospitals may provide higher quality medical care, which in turn proves that government policy on healthcare is effective at improving the medical system in Japan.